Pressure behavior and heat transfer behavior of air natural convection in an asymmetrically heated vertical channel with a damper. (1st June 2022) - Kim, Koung Moon; Lim, Sun Taek; Kim, Seong Ho; Kim, Haeseong; Jerng, Dong-Wook; Ahn, Ho Seon
Highlights: Air natural convection in vertical parallel plates is investigated based on the previously reported experimental results with controlling the damper installed at the end of the channel. The form loss coefficient of the damper estimated in the natural convection has little difference from the coefficient estimated in the forced convection. In a lab-scale experiment, the thermal stratification of the ambient air is normally positive, and it reduces the flow rate and heat transfer performance. When the film temperature is higher than 100 °C, the Rayleigh number trend changes from increase to decrease as the wall temperature increases in air. In the natural convection condition with controlling damper, it cannot apply conventional heat transfer correlation, which consists of the Rayleigh number, Prandtl number, and Nusselt number. Abstract: The natural convection of air between vertical parallel plates under asymmetrical heating was investigated focusing on the pressure behavior and the heat transfer performance as varying two experimentally controlled parameters, namely, the damper closing angle (0 ∼ 45 °) and the thermal operating condition (1.7 ∼ 6.4 kW). By varying the damper closing angle, the form loss coefficient of the damper was estimated from the measured pressure and the calculated pressure difference relating to the thermal gravity effect. It was verified that the form loss coefficient estimated for natural convection was close to the reported form loss coefficient estimated for forced flow. The thermal stratification of the ambient air was additionally considered in the pressure analysis. In addition, the heat transfer was analyzed in terms of the heat transfer correlation. As the damper angle increased, the heat transfer performance decreased owing the reduced flow rate. However, as the thermal operating condition intensified, the heat transfer performance was increased by the improved flow rate. Interestingly, the trend of the Rayleigh number was the same regardless of the two control parameters, even though an intensifying thermal boundary condition improved the heat transfer performance and an increasing damper closing angle weakened the heat transfer performance, conflictingly. Therefore, the correlation conventionally used for natural convection cannot be applied under the conditions of a high wall temperature and control using a damper because it does not consider the flow rate effect. To consider the flow rate effect additionally in the heat transfer correlation, a correlation based on Jackson's mixed convection correlation is suggested. The suggested correlation predicts the heat transfer performance on each wall by considering the effects of the damper angle and operating condition, simultaneously, within the error of less than 30%.